2022
DOI: 10.1080/22221751.2022.2109517
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric risk and protective factors for serious COVID-19 outcomes among older adults in Shanghai Omicron wave

Abstract: Shanghai has been experiencing the Omicron wave since March 2022. Though several studies have evaluated the risk factors of severe infections, the analyses of BA.2 infection risk and protective factors among geriatric people were much limited. This multicentre cohort study described clinical characteristics, and assessed risk and protective factors for geriatric Omicron severe infections. A total of 1377 patients older than 60 were enrolled, with 75.96% having comorbidities. The median viral shedding time and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 28 publications
5
68
0
1
Order By: Relevance
“…Older adults often have more comorbidities; poor nutrition; and poor heart, lung, and kidney function, resulting in their low natural immunity and susceptibility to viruses (9). Although previous studies have suggested that Omicron has an immune evasion effect on vaccines or antibodies from previous infections (11)(12)(13), the infection and severe illness rates increase drastically when the patient is not vaccinated (8,10). In this study, there was no statistically significant difference in vaccination status (35 unvaccinated persons) (P = 0.058), which may be related to the smaller sample size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Older adults often have more comorbidities; poor nutrition; and poor heart, lung, and kidney function, resulting in their low natural immunity and susceptibility to viruses (9). Although previous studies have suggested that Omicron has an immune evasion effect on vaccines or antibodies from previous infections (11)(12)(13), the infection and severe illness rates increase drastically when the patient is not vaccinated (8,10). In this study, there was no statistically significant difference in vaccination status (35 unvaccinated persons) (P = 0.058), which may be related to the smaller sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Although incidences of severe illness and mortality induced by Omicron were lower than previous variants, it was more transmissible and less well-controlled by vaccination ( 6 , 7 ). The high infectivity made the Omicron threaten more people, especially for elderly ( 8 , 9 ), and one study have demonstrated that rate of severe illness would not be decreased for some population without vaccination ( 10 ). Experimental studies show that Omicron has many mutations in its structure compared with SARS-CoV-2, which increases the risk of reinfection ( 2 , 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have found that age has a direct effect on the risk of severe COVID-19 disease [ 22 , 23 ]. We find that the proportion of the elderly cohort in our data set who were hospitalized is much higher than the proportion of the younger cohort (Figure S7 in multimedia Appendix 1).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings comparing vaccine types are similar to those reported by the Centers for Disease Control and Prevention for mortality but provide additional information by vaccine type [ 1 , 16 ]. There have been several studies on individual risk factors such as age [ 22 ], specific comorbidities [ 7 ], focused populations such as Veterans [ 24 ], or large-scale projects such as OpenSAFELY, which involved 17 million unvaccinated patients [ 10 ]. Our work advances this body of literature by analyzing vaccine type, age, sex, and 39 different comorbidities in a large cohort of breakthrough patients from the general US population.…”
Section: Discussionmentioning
confidence: 99%